ANALISIS PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA PT UNIVERSAL FOOTWEAR UTAMA INDONESIA AKIBAT KEPAILITAN PERUSAHAAN BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (STUDI KASUS PUTUSAN NOMOR 12/PDT.SUS-PKPU/2016/PN. NIAGA.JKT.PST) - Marchel Thobie; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2019)
The case faced in writing this scientific paper is how the legal protection of the workers of PT Universal Footwear Utama Indonesia who were declared bankrupt in Decision No. 12/Pdt.Sus-PKPU/2016/PN.Niaga. Jkt Ps t who have not paid salaries for 3 months and severance pay until now in 2018 and how the responsibility of the curator for the bankruptcy of PT Universal Footwear Utama Indonesia after auctioning off the auction for salaries and severance labor. The research method used in this study is normative legal research. The results showed that the legal protection of the workers of PT Universal Footwear Utama Indonesia who were declared bankrupt in Decision No. 12/Pdt.Sus-PKPU /2016/PN.Niaga/Jkt.Pst who have not paid salaries for 3 months and severance pay until now in 2018, in principle all wages of arrears of workers (employee salaries) must be paid after the assets of the bankrupt Debtor have sold and the Distribution list has been determined by the Court on the proposal of the curator. The responsibility of the curator for the bankruptcy of PT Universal Footwear Utama Indonesia after the bankruptcy of the auction was sold against the salary and severance of employment was based on Article 74 of the Bankruptcy Act. The task of the curator is to share the proceeds of the sale of bankruptcy to the creditors in the order (their respective ranks